The effect of a polycarboxylate ether on C3A / CaSO4·2H2O passivation monitored by optical spectroscopy. (8th February 2021) - Ramírez, Alejandra; Pauli, Jutta; Crasselt, Claudia; Simon, Sebastian; Schmidt, Wolfram; Resch-Genger, Ute
Graphical abstract: Highlights: Analysis of cement hydration by fluorescence and diffuse reflectance spectroscopy. The applied cyanine dye proofed itself to be a suitable and stable optical probe. Optical visualization of the initial retardation of the hydration of C3A caused by PCE. Monitoring the formation of metastable phases and changes in ettringite formation. Alternative screening method for comparing the effects of different PCEs in the future. Abstract: Polycarboxylate ethers (PCEs) are widely used in construction, but the exact nature of their interaction with cement is still debated. Aiming at a better understanding of the role of tricalcium aluminate (C3 A) in cement hydration, we assessed the potential of optical spectroscopy in combination with a water-soluble fluorescent organic reporter dye (S0586) to monitor the early hydration of C3 A in the presence of 26 wt% CaSO4 ·2H2 O (C3 A26G-S) with and without PCE. As optical methods, steady-state fluorescence and diffuse reflectance (UV–VisDR) spectroscopy were employed. Phase characterization and particle size distribution were performed with in-situ X-ray diffraction (in-situ XRD) and dynamic light scattering (DLS). Our results show that fluorescence and UV–VisDR spectroscopy can be used to monitor the formation of metastable phases by the disaggregation of the dye S0586 in a cement paste as well as changes in ettringite formation. Addition of PCE slowed down the disaggregation of the dye as reflected by the corresponding changes of the dyes absorption and fluorescence. This prolonged induction period is a well-known side effect of PCEs and agrees with previous reported calorimetric studies and the inhibition of gypsum dissolution observed by in-situ XRD. This demonstrates that fluorescence and UV–VisDR spectroscopy together with a suitable optical probe can provide deeper insights into the influence of PCE on C3 A-gypsum hydration which could be e.g., utilized as screening method for comparing the influences of different types of PCEs.